Repair of major road embankment failure using reinforced earth (RE) wall / Damanhuri Jamalludin ... [et al.] - Jamalludin, Damanhuri; Ahmad, Mohd Farid; Mohd Salleh, Samsuri; Md. Issa, Ahmad Kamal (2015)
A case history of repair works of major road embankment failure along Genting Highlands to Bukit Cincin, Pahang is presented. Failures at 10 locations along Genting Highlands to Bukit Cincin road occurred on 30th October 1997 during the monsoon seasons.